2020
DOI: 10.1108/sjme-01-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Trust and loyalty in online brand communities

Abstract: Purpose The purpose of this paper is to analyse the effects of brand trust and online brand community (OBC) trust on consumer repurchase intention and the positive electronic word-of-mouth (eWOM) intention of OBC members. Design/methodology/approach The research model was assessed using data from a sample of 628 OBC users using partial least squares structural equation modelling (PLS-SEM). Findings The results show that brand trust positively affects repurchase intention and positive eWOM intention, both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 73 publications
(90 reference statements)
2
31
0
10
Order By: Relevance
“…Thus, it may be assumed that community members' trust toward the brand should motivate them to exchange information [50]. Various studies in the field of OBCs show the positive relationship between the generation of brand trust and members' willingness to propagate positive WOM about the brand [3,79,87]. Thus, the following hypothesis is proposed: Hypothesis 11 (H11).…”
Section: Positive Wommentioning
confidence: 99%
“…Thus, it may be assumed that community members' trust toward the brand should motivate them to exchange information [50]. Various studies in the field of OBCs show the positive relationship between the generation of brand trust and members' willingness to propagate positive WOM about the brand [3,79,87]. Thus, the following hypothesis is proposed: Hypothesis 11 (H11).…”
Section: Positive Wommentioning
confidence: 99%
“…Authors such as Reichheld and Markey (2000) state that highly satisfied customers will not necessarily be loyal. Nowadays, entities are worried that current consumers tend to be less loyal (Dekimpe et al , 1997; Kapferer, 2005; Bennett and Rundle-Thiele, 2004, Anaya-Sánchez et al , 2020). This makes it necessary to introduce new variables into the model that will positively influence consumer loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…Prior hospitality-based research has shown that eWOM acts as a social influence on customer behaviors (Book and Tanford, 2019). Previous studies have analyzed the effect of eWOM on customer responses, such as attitudes (Casaló et al , 2015a; Vermeulen and Seegers, 2009), intentions (Ruiz-Equihua et al , 2019; Sparks and Browning, 2011), trust (Anaya-Sánchez et al , 2020) and engagement (Kanje et al , 2020). However, there may be differences in the impact of eWOM on customer behaviors in the hospitality context based on generational cohort.…”
Section: Introductionmentioning
confidence: 99%